Pharmacoinvasive strategy versus fibrinolytic therapy alone in adults with ST-elevation myocardial infarction: A systematic review and meta-analysis - David R. Soriano-Moreno; Kimberly G. Tuco; Carolina J. Delgado Flores; Kevin Flores-Lovon; Fabricio Ccami-Bernal; Renatta Quijano-Escate; Luis Marcos López-Rojas; Sergio Goicochea-Lugo (PLoS ONE, 2025)
Objective To compare the pharmacoinvasive strategy (PS) versus fibrinolysis alone in adults with ST-segment elevation myocardial infarction. Methods We searched PubMed/MEDLINE, Web of Science, Embase, and Cochrane Library from inception until January 17th, 2025. The review protocol was registered in PROSPERO (CRD42022309130). We included randomized controlled trials (RCTs), assessed risk of bias with the Cochrane Risk of Bias 1.0 tool, and calculated pooled relative risks and mean differences. We used GRADE’s minimally contextualized approach to determine the certainty of the evidence. Results We found 7 RCTs (n = 3053). The PS, compared to fibrinolysis alone, may have an important reduction on mortality (3.3% vs 3.9%; −5 per 1000; 95% CI: −16 to +10); and has an important reduction on reinfarction (2.6% vs 4.4%; −19 per 1000; 95% CI: −27 to −6), revascularization (9.0% vs 26.8%; −169 per 1000; 95% CI: −220 to −64), and recurrent ischemia (1.2% vs 5.7%; −46 per 1000; 95% CI: −52 to −27) at 30 days follow up. Similar results were found at longest follow up for the outcomes mentioned. PS probably has an important reduction on mean hospital stay length at longest follow up (−2.47 days; 95% CI: −4.17 to −0.78) and may reduce cardiac failure and cardiogenic shock at 30 days, but the evidence is very uncertain. PS has trivial or no effect on major bleeding (4.6% vs 5.0%; −4 per 1000; 95% CI: −17 to +13) and may have an important reduction on stroke (0.7% vs 1.3%; −6 per 1000: 95 CI: −10 to +2). Conclusions The PS has an important reduction on reinfarction, revascularization, and recurrent ischemia; probably has an important reduction on mean hospital stay length; and may have an important reduction of mortality and stroke. Also, PS may reduce cardiac failure and cardiogenic shock, but the evidence is very uncertain. The risk of major bleeding did not increase.